Macro Conditions for the Functioning of a Joinery Production Company in the Situation of an Unpredictable Economic Slowdown - Paweł POSADZY; Joanna KAŁKOWSKA (Communications of International Proceedings, 2020)
The basis of the functioning of every enterprise is its ability to move efficiently and effectively in the business space. This ability depends on a number of conditions, both intra-sectoral, on which the company can have a direct impact, as well as macro-environmental, political and legal, cultural and social, economic and technological and organizational. The analysis of macro-environmental conditions can be a determinant of wise use of company's resources and lead to success despite the change of its macro-environment. In the article such an analysis was carried out in relation to a particular joinery manufacturing company in a situation of a pandemic economic slowdown. This analysis for the adopted case study allowed to determine the magnitude of the forces of positive and negative impact of individual macro- conditions.
Keywords: Strategic Analysis; Macroenvironment of an Enterprise.